Sex- and Metamorphosis-Related Changes in the Cuticular Lipid Profile of Galleria mellonella Pupae and Adults - Mieczysława I. Boguś; Michalina Kazek (Insects)
The majority of insects reproduce sexually. Among the many factors involved in controlling the reproductive process, cuticular lipids play an important role as unique chemical signatures of species, developmental stage, and sex, and participate in mate recognition. An understanding of the sex- and metamorphosis-related fluctuations in the cuticular lipid profiles of harmful insects is necessary to hamper their reproductive process. A GC/MS analysis of the cuticular lipids of the beehive pest Galleria mellonella Linnaeus (Lepidoptera: Pyralidae) revealed 11 FFAs in the male pupae (C8:0, C9:0, C14:0, C15:0, C16:1, C16:0, C17:0, C18:1, C18:0, C20:1, and C21:1) together with another two in the females (C10:0 and C17:1). As metamorphosis progressed, some FFAs disappeared from the pupal cuticle (C8:0 and C17:0 in both sexes, and C10:0, C17:1, and C20:1 only in female pupae) and the levels of the others changed. In adult virgin males and females, C8:0, C17:1, and C17:0 reappeared and two FFAs absent in pupae (C6:0 and C11:0) appeared. In virgin males, C13:0 also appeared (absent in pupae). Copulation resulted in the disappearance of C13:0 and C17:1, decreased the concentrations of C9:0, C11:0, C18:1, and C18:0, and elevated the amounts of C14:0, C16:1, and C16:0 in mated males. In mated females, the concentrations of C11:0, C14:0, C15:0, C16:0, C17:1, and C18:1 increased while C18:1 decreased. Copulation reduced cholesterol levels in mated females, and increased those in males.